Vitalidad del Dios trinitario según Juan de Ávila - García Mateo, Rogelio (Estudios eclesiásticos, 2010)
The Work of St. Juan de Ávila (1499-1559) aims at his pastoral ministry. His theology, inspired mainly in the Bible, was intended to explain the great mysteries of Faith and to show its relevance for Christian life. For him, who had among his hearers a good number of Jews converted to Christ, it was of outmost importance to explain the mystery of Holy Trinity, and to prove that this Dogma does not contradict, but enriches the understanding of monotheism.